Depth analysis of Al/ZrC interfaces using SIMS and x‐ray reflectivity. (17th April 2018) - Modi, Mohammed H.; Sinha, Mangalika; Bose, Aniruddha; Singh, Amol; Jonnard, Philippe
Abstract : Al/ZrC/Al/W multilayer structure is suitable for waveguide applications in the hard X‐ray region in order to confine the wave field in a nanometer‐thick layer. Intermixing of Al at the interfaces is a serious problem to achieve the expected performances from an experimentally grown multilayer. In the present study, the effect of a carbon capping layer in a C/Al/ZrC/Al/W waveguide structure is determined using time of flight secondary ion mass spectrometry (SIMS) and soft X‐ray reflectivity techniques. Structural parameters i.e., density, thickness, and roughness of the layers are determined using soft X‐ray reflectivity data. SIMS results indicate that the Al diffusion towards the top of the stack is responsible for the formation of a wide and asymmetric interfaces in the waveguide structure.